Total synthesis of protosappanin A and its derivatives via palladium catalyzed ortho C–H activation/C–C cyclization under microwave irradiation. Issue 29 (21st March 2016) - Liu, Jiaqi; Zhou, Xuan; Wang, Chenglong; Fu, Wanyong; Chu, Wenyi; Sun, Zhizhong
Abstract : Protosappanin A, a complex natural product with high bioactivity, and 25 of its derivatives were synthesized through an intramolecular ortho C–H activation/C–C cyclization, ring-enlargement and deprotection reaction. C–H activation as the key step was investigated and optimized. Abstract : A total synthesis method for protosappanin A, which is a complex natural product with many biological activities, was developed with 6 linear steps. Dibenzo[ b, d ]oxepinones as the key intermediates of the synthetic route were prepared by a palladium-catalyzed ortho C–H activation/C–C cyclization under microwave irradiation. 25 derivatives of protosappanin A were obtained.